The Word Anjum In The Poetic Book Bang-E-Dara Written By Alama Iqbal - Neelam; Hassan, Nadeem (sourcecoder, 2023)
The circumstances and events of this period and the decline of Muslims played an important role in Iqbal's mental formation. If Iqbal's poetry is studied from the beginning, it comes out that he started with poetic poetry, but soon abandoned the themes of traditional poetry and wrote poetry for the reformation of the nation. His poetry awakened the Muslims so much. The book "Bang Dara" was indeed a wake-up call for the fallen Muslim caravan. In all these poems, the same philosophy of Iqbal can be seen. Iqbal has revealed the secret of national life through the language of stars, that is, he has made this fact clear that Muslims, if they want to develop as a nation, should learn from the life of stars. Their system is mutual absorption. It is established by the same way that Muslims can also develop due to mutual cooperation.